Hubungan Kinerja Kader Dan Persepsi Dengan Minat Pasangan Usia Subur Mengikuti Program Keluarga Berencana Di Desa Cisait Kecamatan Kragihan - Ajeng Ramdani, Febryan; Kamil, Mustofa; Suhifatullah, M.I. (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2024)
This research is a quantitative study which aims to find out whether there is a positive and significant relationship between: 1) cadre performance and the interests of couples of childbearing age, 2) perceptions and the interests of couples of childbearing age, and 3) cadre performance and perceptions and the interests of couples of childbearing age. The sampling technique used was simple random sampling. Data was collected through questionnaires and analyzed using the SPSS ver. 22. The research results show that: 1) there is a positive and significant relationship between cadre performance and the interest of couples of childbearing age where the significance value is 0.038 (p-value < 0.05) and the correlation coefficient is 0.242, 2) there is a positive and significant relationship between perceptions with the interest of couples of childbearing age where the significance value is 0.000 (p-value <0.05) and the correlation coefficient is 0.665, and 3) there is a relationship between cadre performance and perception together with the interest of couples of childbearing age where the significance value is 0.000 (p- value < 0.05) and a correlation coefficient of 0.674. Keywords: Interest of childbearing couples, cadre performance, perception.